The Politics of Female Reading in Jane Austen’s Northanger Abbey - Simon, Rebeka (FOCUS: Papers in English Literary and Cultural Studies, 2025)
The essay discusses Northanger Abbey (1817) by Jane Austen as a site for interrogating the gendered politics of reading in the late eighteenth and early nineteenth centuries. Focusing on the figure of Catherine Morland, it argues that Austen’s novel participates in contemporary debates about female literacy, novel consumption, and the cultural anxieties surrounding women’s affective engagement with novels. Drawing on Janice Radway’s concept of reading as affective negotiation within patriarchal structures, and informed by the cultural materialist framework of Jonathan Dollimore and Alan Sinfield, the essay contends that Northanger Abbey portrays female reading as a conflicted practice, simultaneously enabling imaginative agency and reinforcing normative social roles. Rather than simply parodying Gothic conventions or defending the novel, Austen uses Catherine’s reading habits to reflect on the ideological contradictions embedded in fictional representation. Catherine’s transition from naïve Gothic reader to an increasingly self-aware subject dramatizes the disciplinary potential of reading. The novel stages this transformation not through a repudiation of fiction, but through a recontextualization of interpretive practice. In doing so, Northanger Abbey resists reductive binaries of education and escapism, suggesting instead that women’s reading constitutes a dynamic cultural negotiation.